External reporting of human capital in Malaysia - Huang, Ching Choo; Zainal Abidin, Zubaidah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
Human capital information which is vital for effective management of resources is usually only accessible internally within an organization. However, information regarding human capital or human resource investments and the return on these investments are currently not presented in the annual reports systematically and consistently. This paper examines the extent of the disclosure of human capital in the annual reports of Malaysian top companies based on the concept of Human Resource Costing and Accounting (HRCA) and other relevant human capital elements or measures. A content analysis using word count was conducted to determine the extent of human capital disclosures. The findings reveal that the concept of HRCA is still distant to human resource managers in Malaysia. The human capital items which are most commonly disclosed are information on training, human resource development, employee skill, knowledge and competence. Return on human resource investment is not reported in the annual reports.